Das Angesicht des Herrschers.: Frühmittelalterliche Beispiele von Fehlen und Vorhandensein bildlicher Repräsentation im Vergleich - Schwedler, Gerald (Comparativ, 2008)
Different strategies of visual representation of rulers can be observed on the basis of a close analysis of images on coins produced in the early middle ages. The propagandistic use of ruler images is related to theological debates on the feasibility and appropriateness of visual representations, e. g. the Byzantine iconoclastic controversy or the Islamic ban on figurative images. The transcultural comparison of visual representations is based on sources from Byzantium, the Latin West and the Islamic caliphate of the Umayyads and Abbasids in the 7th and 8th centuries.